South African Children: A Matched Cohort Study of Neurodevelopmental Impairment in Survivors of Invasive Group B Streptococcus Disease Aged 5 to 8 Years. (2nd November 2021) - Harden, Lois M; Leahy, Shannon; Lala, Sanjay G; Paul, Proma; Chandna, Jaya; Lowick, Sarah; Mbatha, Sibongile; Jaye, Tamara; Laughton, Barbara; Ghoor, Azra; Sithole, Pamela; Msayi, Jacqueline; et al.
Abstract: Background: Invasive group B Streptococcus (iGBS) sepsis and meningitis are important causes of child mortality, but studies on neurodevelopmental impairment (NDI) after iGBS are limited. Using Griffiths Mental Development Scales–Extended Revised (GMDS-ER), we described NDI in iGBS survivors and non-iGBS children from South Africa, as part of a 5-country study. Methods: We identified children aged 5–8 years with a history of iGBS and children with no history of iGBS between October 2019 and January 2021. Children were matched on sex, and birth data (month, year) (matched cohort study). Moderate or Severe NDI was the primary outcome as a composite of GMDS-ER motor, GMDS-ER cognition, hearing, and vision. Secondary outcomes included mild NDI, any emotional-behavioral problems, and GMDS-ER developmental quotients (DQ) calculated by dividing the age equivalent GMDS-ER score by the chronological age. Results: In total, 160 children (iGBS survivors, 43; non-iGBS, 117) were assessed. Among iGBS survivors 13 (30.2%) had meningitis, and 30 (69.8%) had sepsis. Six (13.9%) iGBS survivors, and 5 (4.3%) non-iGBS children had moderate or severe NDI. Children who survived iGBS were 5.56 (95% confidence interval [CI]: 1.07–28.93; P = .041) times more likely to have moderate or severe NDI at 5–8 years than non-iGBS children. Compared to the non-iGBS children, iGBS meningitis survivors had a significantly lower global median DQ ( P  < .05), as well as a lower median DQ for the language GMDS-ER subscale and performance GMDS-ER subscale ( P  < .05). Conclusions: Children surviving iGBS, particularly meningitis, are more likely to have NDI at 5–8 years compared to non-iGBS children. Further research is required to improve detection and care for at-risk newborns.